Captivating the cynical earl - Tinley, Catherine (Tinley, Catherine. Ladies of Ledbury House., 2021)
"For Jack Beresford, Earl of Hawkenden, emotional entanglements are the path to pain. But when his brother brings his new wife and her best friend to his country home, everything changes. Lady Cecily Thornhill is both vibrant and beautiful, and Jack finds himself increasingly captivated by her sunny nature. Yet he must resist her charms, for in a month she'll be gone--unless his frozen heart thaws before then..."--